7th grade math....

How many positive factors does 100 have

Posted on Jun 05, 2009

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

5x-y=-5 answer x=-1, y= 5
http://www.wolframalpha.com/input/?i=Determine+the+x+and+y+intercept+of+the+graph+for+equation%3A+5x-y%3D-5

-3x+2y=7 answer x = -7/3, y = 7/2 http://www.wolframalpha.com/input/?i=Determine+the+x+and+y+intercept+of+the+graph+for+equation%3A+-3x%2B2y%3D7

-3x+2y=7 answer x = -7/3, y = 7/2 http://www.wolframalpha.com/input/?i=Determine+the+x+and+y+intercept+of+the+graph+for+equation%3A+-3x%2B2y%3D7

Feb 23, 2015 | Office Equipment & Supplies

dy/dx = e^(3x + 2y) = (e^3x)(e^2y)

INT e^-2y dy = INT e^3x dx

Can you finish it from there? Don't forget constant of integration.

I hope this helps!

INT e^-2y dy = INT e^3x dx

Can you finish it from there? Don't forget constant of integration.

I hope this helps!

May 06, 2011 | Computers & Internet

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

And your question is? If you just want to know how to solve this system, you only need to substitute one equation into the other and solve for the remaining unknown.

y=3x (equation 2), so plug it into equation 1

7x-2y=1

7x-2(3x)=1

7x-6x=1

x=1

from equation 2 then, you know y=3x=3

y=3x (equation 2), so plug it into equation 1

7x-2y=1

7x-2(3x)=1

7x-6x=1

x=1

from equation 2 then, you know y=3x=3

Oct 05, 2010 | Linear (HDMICAT5EXT) Repeater

3x(3x)/2y+(3x) - 3x-2y/3x+2y

Jan 25, 2010 | Acer Office Equipment & Supplies

Hello,

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

Oct 01, 2009 | The Learning Company Achieve! Math &...

Hi joanmae jmeh;

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

Dec 01, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

(x+3y=0)*3=3x+9y

y=1 x= -3

y=1 x= -3

Jun 29, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

1,229 people viewed this question

Usually answered in minutes!

would you please show the steps in solving

3x + 2y = -6

thank you for your help

×